Prospective longitudinal characterisation of the relationship between diabetes and cardiac remodeling. (13th July 2021) - Chowdhary, A; Jex, N; Thirunavukarasu, S; Craven, T; Das, A; Gorecka, M; Saunderson, C; Greenwood, JP; Swoboda, PP; Plein, S; Levelt, E
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation Clinical Research Training Fellowship and Wellcome Trust Background: Cardiovascular disease represents the primary cause of death in patients with type 2 diabetes (T2D). Heart failure (HF) is the commonest initial presentation of cardiovascular disease in T2D. Development of HF in patients with T2D is associated with a 4 to 6-fold increase in mortality, making the prevention of cardiac dysfunction an important goal. The long-term impact of T2D on cardiac function in the absence of cardiovascular disease is unknown. This is the first prospective longitudinal study utilising cardiovascular magnetic resonance (CMR) to evaluate the impact of T2D on cardiac remodeling. Objectives: To determine longitudinal changes in the phenotypic expression of heart disease in diabetes over 6 years, and examine the association of baseline blood and imaging biomarkers with remodeling over time in patients who remained free of cardiovascular/clinical events, and to report clinical outcomes in the entire cohort. Methods: 100 asymptomatic T2D patients with no history of cardiovascular disease or hypertension were previously studied. Biventricular volumes, function, and myocardial strain were assessed by CMR and blood biomarkers taken. 6-year follow-up CMR was repeated in those without interim cardiovascular events. Results: Of the 100 patients, 78 could be contacted for follow-up. 29 participants experienced cardiovascular/clinical events over 6 years. 32 patients who were asymptomatic and without events received follow-up CMR. The major adverse cardiovascular event rate (MI, angina, revascularisation, stroke, death) during the 6-year follow-up period, including the patients with a silent MI, amounted to 25% in this study with an overall clinical event rate of 35%.  There were no significant changes in BP, BMI or HBA1c between baseline and follow-up (Table 1). Left ventricular end-diastolic-volume(p = 0.005), mass (p = 0.01), ejection fraction (p = 0.0001), and right ventricular end-diastolic-volume(p = 0.03) and ejection fraction(p = 0.003) reduced over time (Figure 2 and Table 1). Baseline plasma high-sensitivity cardiac-troponin-T (hs-cTnT) (R=-0.44; p = 0.01) was significantly associated with change in left ventricular ejection fraction over time. Conclusions: Even in the absence of overt clinical CAD, significant valvular disease, uncontrolled hypertension or change in BMI, T2D results in significant reductions in cardiac size and biventricular systolic function over time. The major adverse cardiovascular event rate (MI, angina, revascularisation, stroke, death) during the 6-year follow-up period was high in diabetes patients (25%). Plasma biomarker hs-cTnT measured at baseline was associated with change in LV systolic function over the 6-year follow-up period. hs-cTnT could potentially have a significant utility as a risk-predicting tool for cardiac dysfunction in T2D patients.